Respuesta :

Simplifying

64 + -12w = 6w

Solving

64 + -12w = 6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6w' to each side of the equation.

64 + -12w + -6w = 6w + -6w

Combine like terms: -12w + -6w = -18w

64 + -18w = 6w + -6w

Combine like terms: 6w + -6w = 0

64 + -18w = 0

Add '-64' to each side of the equation.

64 + -64 + -18w = 0 + -64

Combine like terms: 64 + -64 = 0

0 + -18w = 0 + -64

-18w = 0 + -64

Combine like terms: 0 + -64 = -64

-18w = -64

Divide each side by '-18'.

w = 3.555555556

Simplifying

w = 3.555555556